An historical study of the Ministry of Federal Territories building in Putrajaya within the perspective of the discourse on the national and Islamic architectural identity of administrative architecture - Mohd Rasdi, Mohd Tajuddin; Kanesh, Kevin; Utaberta, Nangkula; Asif, Nayeem (Knowledge E, 2020)
The establishment of a new administrative center in Putrajaya, offered an opportunity to address and to reaffirm a national architectural identity. This research attempts to document and evaluate the design direction of administrative buildings in Putrajaya in response to the issue of establishing a national architectural identity. This paper attempts to analyze the various inputs towards achieving the desired image, from the political, socio-cultural and economic contexts. Additionally, this study considers the thoughts and standpoint of the architect that was in charge of the design for the selected administrative building. This research uses a historical architectural interpretative methodology to analyze the building in situ along with literature reviews and interviews with key stakeholders. The data obtained and presented reveals the underlying issues and convictions that contributed to the formation of a national architectural identity. The research demonstrates how the architect’s design sought to emphasise the local and Islamic characteristics and thereby highlight the role of Islam within the new administrative center of Malaysia. This research will provide a critical approach to evaluate the underlying issues which help to form a national architectural identity.